Macroeconomic implications of uniform pricing - Daruich, Diego and Kozlowski, Julian (American Economic Journal: Macroeconomics)
We compile a new database of grocery prices in Argentina. We find uniform pricing both within and across regions$1 (Bi.e., prices almost do not vary within the stores of a chain. In line with uniform pricing, prices in stores of chains operating in one region react to changes in regional employment while prices in multiregion chains do not. Using a quantitative regional model with multiregion firms and uniform pricing, we find a one-half smaller elasticity of prices to a regional than an aggregate shock. This result highlights that some caution may be necessary when using regional shocks to estimate aggregate elasticities.- Reproduced s
Keywords: PRICING